Polishing composition
By using a modified polyvinyl alcohol-based polymer and a chelating agent in the polishing composition, the problem of difficult to balance the polishing rate and surface quality in the prior art is solved, and the combination of efficient polishing and high-quality surfaces is achieved.
Patent Information
- Application Number
- CN202380057164.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-05
- Filing Date
- 2023-07-28
- Publication Date
- 2025-03-18
AI Technical Summary
The existing grinding compositions are difficult to achieve high-quality surfaces while increasing the grinding rate, and there is a problem of reducing defects after grinding (such as LPD-N).
The polishing composition including silica particles, alkaline compounds, modified polyvinyl alcohol-based polymers and chelating agents is adopted. The etching rate of the modified polyvinyl alcohol-based polymer is 20 nm/h or less, so that the surface of the polishing object is protected, defects are reduced, and the polishing rate is increased by the chelating agent.
While maintaining the grinding rate, the surface quality after grinding is significantly improved, the defects of the grinding surface are reduced, and the surface finish is improved.
Smart Images

Figure BDA0005259519480000111 
Figure BDA0005259519480000421
Abstract
Description
Technical Field
[0001] The present invention relates to a polishing composition. This application claims priority based on Japanese Patent Application No. 2022-125594 filed on August 5, 2022, the entire contents of which are incorporated herein by reference. Background Art
[0002] A polishing composition is used to precisely grind the surface of a material such as a metal or semi-metal, a non-metal, or an oxide thereof. For example, the surface of a silicon wafer used as a component of a semiconductor device is usually finished into a high-quality mirror surface through a grinding process (rough grinding process) and a polishing process (precision grinding process). The polishing process typically includes a pre-polishing process (pre-grinding process) and a fine polishing process (final grinding process). As technical documents related to the polishing composition mainly used in the use of grinding semiconductor substrates such as silicon wafers, patent documents 1 to 3 can be cited.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent No. 6185432
[0006] Patent Document 2: Japanese Patent No. 6348927
[0007] Patent Document 3: Japanese Patent No. 6232243 Summary of the invention
[0008] Problem that the invention aims to solve
[0009] In the grinding composition, a composition with a grinding ability to grind the grinding object efficiently is used. For example, when grinding a substrate such as a semiconductor substrate such as the above-mentioned silicon wafer, the mechanical grinding effect produced by the abrasive and the chemical grinding effect (alkali etching) produced by the alkaline compound can be used to exert a higher processing force. The grinding composition with high processing force can improve manufacturing efficiency and cost-effectiveness, which is preferred. In this grinding, by using silicon dioxide particles as abrasives, a grinding surface with good quality can be efficiently achieved.
[0010] In addition, the grinding composition used for grinding the above-mentioned substrate, such as the grinding composition used for the fine polishing process (especially the fine polishing process of semiconductor substrates such as silicon wafers and other substrates), is required to achieve high-quality surface performance after grinding. The improvement of the surface quality after grinding can be achieved by making the grinding composition contain a water-soluble polymer, and using the above-mentioned water-soluble polymer to protect the substrate from alkali etching. For example, patent documents 1 to 3 disclose a grinding composition, which includes silica particles, an alkaline compound and a water-soluble polymer. However, in the prior art, there is still room for improvement in reducing defects after grinding (such as LPD-N (Light Point Defect Non-cleanable, non-cleanable light point defects)) and improving surface quality. In addition, usually improving the quality of the grinding surface is in a trade-off relationship with the grinding rate. Therefore, if a grinding composition that can improve the surface quality after grinding while maintaining the grinding rate can be realized, it is beneficial in practical application, for example, it is particularly beneficial in the fine polishing process.
[0011] Therefore, an object of the present invention is to provide a polishing composition comprising a water-soluble polymer, which can achieve a high-quality surface while maintaining a polishing rate.
[0012] Solutions for solving problems
[0013] According to the present specification, a polishing composition is provided. The polishing composition comprises: silica particles (A) as abrasive particles, a basic compound (B), a water-soluble polymer (C) and a chelating agent (D). Here, the water-soluble polymer (C) comprises a modified polyvinyl alcohol polymer (C1) having an etching rate of 20 nm / hour or less.
[0014] Here, the etching rate is an index for evaluating the performance of a water-soluble polymer (eg, a modified polyvinyl alcohol-based polymer) in protecting the surface of an object to be polished from corrosion (etching) caused by an alkali. The etching rate is determined based on the following etching rate measurement.
[0015] [Etching rate measurement]
[0016] (1) A chemical solution LE for measuring an etching rate containing 0.175 wt % of a modified polyvinyl alcohol polymer and 0.205 wt % of ammonia, with the balance being water, was prepared.
[0017] (2) Prepare a silicon single crystal substrate (rectangular shape with a length of 6 cm, a width of 3 cm, and a thickness of 775 μm) and measure its weight W0. The silicon single crystal substrate is immersed in a cleaning solution of NH4OH (29%):H2O2 (31%):deionized water (DIW) = 2:5.3:48 (volume ratio) at 25°C for 1 minute, and then immersed in a hydrogen fluoride (HF) aqueous solution (5%) at 25°C for 30 seconds.
[0018] (3) immersing the silicon single crystal substrate in the chemical solution LE at 25° C. for 40 hours;
[0019] (4) taking out the silicon single crystal substrate from the chemical solution LE and washing it with deionized water (DIW) at 25° C. for 10 seconds;
[0020] (5) The weight W1 of the cleaned silicon single crystal substrate is measured.
[0021] (6) The etching rate [nm / hour] is calculated based on the difference between W0 and W1 and the specific gravity of the silicon single crystal substrate.
[0022] A low etching rate indicates that the water-soluble polymer has a high performance in protecting the surface of the polishing object from corrosion caused by alkali. According to the polishing composition of the above constitution, since a modified polyvinyl alcohol-based polymer having a high performance in protecting against corrosion caused by alkali is used, there is a tendency that the surface of the silicon wafer as the polishing object is protected and defects (such as LPD-N) after polishing are reduced. Furthermore, by using a chelating agent together with the modified polyvinyl alcohol-based polymer, there is a tendency that a high-quality surface with reduced defects (such as LPD-N) after polishing can be achieved while maintaining the polishing rate.
[0023] In some embodiments, the modified polyvinyl alcohol polymer (C1) is at least one selected from the group consisting of acetalized polyvinyl alcohol polymers and polyvinyl alcohol polymers containing repeating units derived from alkyl vinyl ethers. Such specific modified polyvinyl alcohol polymers tend to have a high performance in protecting the surface of the polishing object from corrosion caused by alkali, and are likely to improve the quality of the surface of the polishing object after polishing.
[0024] In some embodiments, the content of the modified polyvinyl alcohol polymer (C1) is 0.5 parts by weight or more and 10 parts by weight or less based on 100 parts by weight of the abrasive. According to this composition, the effects of the technology disclosed herein can be preferably achieved.
[0025] In some embodiments, the polishing composition further comprises a water-soluble polymer (C2) having a chemical structure different from that of the modified polyvinyl alcohol polymer (C1) as the water-soluble polymer (C). By using the modified polyvinyl alcohol polymer (C1) in combination with the water-soluble polymer (C2), it is expected that the polishing rate will be improved, defects will be suppressed, and other effects will be achieved. In some embodiments, as the water-soluble polymer (C2), a polymer containing nitrogen atoms can be used. In the polishing composition disclosed herein, when the modified polyvinyl alcohol polymer (C1) and the polymer containing nitrogen atoms are used in combination, there is a tendency that the polishing rate is easily improved. As the polymer containing nitrogen atoms, for example, a polymer containing a cyclic amide having an N-(methyl)acryloyl group as a monomer unit can be preferably used.
[0026] In some embodiments, as the chelating agent (D), one or more selected from aminocarboxylic acid chelating agents and organic phosphonic acid chelating agents can be used. In the technology disclosed herein, by using the above-mentioned specific chelating agent, a polishing composition that can further reduce defects after polishing while maintaining the polishing rate can be achieved.
[0027] In some embodiments, the polishing composition further comprises a surfactant (E). According to this configuration, the surface quality after polishing tends to be further improved. In a preferred embodiment, the surfactant (E) is an anionic surfactant.
[0028] The polishing composition disclosed herein can be preferably used for polishing a surface formed of a silicon material. By polishing a surface formed of a silicon material using the polishing composition, a high-quality surface formed of a silicon material can be efficiently achieved.
[0029] The polishing composition disclosed herein may be a concentrated liquid. The polishing composition disclosed herein may be produced, distributed, and stored in the form of a concentrated liquid.
[0030] In some embodiments, a polishing method is provided for polishing a surface formed of a silicon material using the polishing composition. According to the polishing method, a high-quality surface can be achieved while maintaining a polishing rate. DETAILED DESCRIPTION
[0031] The following describes a suitable embodiment of the present invention. It should be noted that matters necessary for the implementation of the present invention other than matters specifically mentioned in this specification can be grasped as conventional means by those skilled in the art based on the prior art in this field. The present invention can be implemented according to the contents disclosed in this specification and the technical common sense in this field.
[0032] <Abrasive grain>
[0033] The grinding composition disclosed herein contains silica particles as abrasive particles. The silica particles as abrasive particles play a role in mechanically grinding the surface of the grinding object. By making the grinding composition contain abrasive particles, the grinding rate can be increased based on the mechanical grinding effect caused by the abrasive particles. In addition, in a grinding composition that can be used for grinding (e.g., fine polishing) of a grinding object having a surface formed of silicon, such as a silicon wafer described later, it is particularly meaningful to use silica particles as abrasive particles.
[0034] As specific examples of silica particles, colloidal silica, fumed silica, precipitated silica, etc. can be cited. The silica particles can be used alone or in combination of two or more. From the aspect of easily obtaining a polished surface with excellent surface quality after grinding, colloidal silica is particularly preferably used. As colloidal silica, for example, colloidal silica made by using water glass (sodium silicate) as a raw material by an ion exchange method, and alkoxide method colloidal silica (colloidal silica manufactured by a hydrolysis condensation reaction of alkoxysilane) can be preferably used. Colloidal silica can be used alone or in combination of two or more.
[0035] The true specific gravity of the silicon dioxide constituting the silicon dioxide particles is preferably 1.5 or more, more preferably 1.6 or more, and further preferably 1.7 or more. The upper limit of the true specific gravity of silicon dioxide is not particularly limited, and is typically 2.3 or less, for example, 2.2 or less. The true specific gravity of the silicon dioxide particles can be a measured value obtained by a liquid substitution method using ethanol as a substitution liquid.
[0036] The average primary particle size of the abrasive (typically silica particles) is not particularly limited, and from the viewpoint of the grinding rate, it is preferably 5 nm or more, more preferably 10 nm or more. From the viewpoint of obtaining a higher grinding effect (such as a reduction in haze, removal of defects, etc.), the above-mentioned average primary particle size is preferably 15 nm or more, more preferably 20 nm or more (for example, more than 20 nm). In addition, from the viewpoint of preventing scratches, the average primary particle size of the abrasive is preferably 100 nm or less, more preferably 50 nm or less, and further preferably 45 nm or less. From the viewpoint of easily obtaining a surface with lower haze, in some embodiments, the average primary particle size of the abrasive can be 43 nm or less, less than 40 nm, less than 38 nm, less than 35 nm, less than 32 nm, or less than 30 nm.
[0037] It should be noted that in this specification, the average primary particle size refers to the specific surface area (BET value) measured by the BET method, and is calculated according to the formula: average primary particle size (nm) = 6000 / (true density (g / cm 3 )×BET value (m 2The above-mentioned specific surface area can be measured using, for example, a surface area measuring device manufactured by Micromeritics, trade name "Flow Sorb II 2300".
[0038] The average secondary particle size of the abrasive (typically silica particles) is not particularly limited, and can be appropriately selected from a range of about 15 nm to 300 nm, for example. From the viewpoint of increasing the grinding rate, the above-mentioned average secondary particle size is preferably greater than 30 nm, and more preferably greater than 35 nm. In some embodiments, the above-mentioned average secondary particle size can be, for example, greater than 40 nm, or greater than 42 nm, and preferably greater than 44 nm. In addition, it is generally advantageous for the above-mentioned average secondary particle size to be less than 250 nm, preferably less than 200 nm, and more preferably less than 150 nm. In some preferred embodiments, the above-mentioned average secondary particle size is less than 120 nm, more preferably less than 100 nm, and further preferably less than 70 nm, for example, less than 60 nm, and also less than 50 nm.
[0039] In this specification, the average secondary particle size refers to the particle size (volume average particle size) measured by the dynamic light scattering method. The average secondary particle size of the abrasive can be measured by the dynamic light scattering method using, for example, Nanotrac UPA-UT151 manufactured by Nikkiso Co., Ltd.
[0040] The shape (outer shape) of the silica particles may be spherical or non-spherical. Specific examples of non-spherical particles include peanut-shaped (i.e., the shape of peanut shells), cocoon-shaped, candy-shaped, rugby-shaped, etc. For example, silica particles having mostly peanut-shaped or cocoon-shaped particles may be preferably used.
[0041] Although not particularly limited, the average value (average aspect ratio) of the major diameter / minor diameter ratio of the silica particles is in principle more than 1.0, preferably more than 1.05, more preferably more than 1.1, and may be more than 1.2. With the increase of the average aspect ratio, a higher polishing rate can be achieved. In addition, from the viewpoint of reducing scratches, the average aspect ratio of the silica particles is preferably less than 3.0, more preferably less than 2.0, more preferably less than 1.5, and may be less than 1.4.
[0042] The shape (outer shape) and average aspect ratio of silica particles can be grasped, for example, by electron microscope observation. As a specific step to grasp the average aspect ratio, for example, a scanning electron microscope (SEM) is used to draw the smallest rectangle circumscribed to each particle image for a specified number (e.g., 200) of silica particles whose independent particle shapes can be identified. Then, for the rectangle drawn for each particle image, the length of its long side (the value of the long diameter) is calculated and divided by the length of the short side (the value of the short diameter) to obtain the value as the long diameter / short diameter ratio (aspect ratio). The aspect ratios of the above-mentioned specified number of particles are arithmetic averaged, thereby obtaining the average aspect ratio.
[0043] The polishing composition disclosed herein may also contain abrasives other than silica particles (hereinafter also referred to as "non-silica abrasives") within a range that does not significantly hinder the effect of the present invention. Examples of non-silica abrasives include inorganic particles, organic particles, and organic-inorganic composite particles. Specific examples of inorganic particles include: oxide particles such as aluminum oxide particles, cerium oxide particles, chromium oxide particles, titanium dioxide particles, zirconium oxide particles, magnesium oxide particles, manganese dioxide particles, zinc oxide particles, and iron red particles; nitride particles such as silicon nitride particles and boron nitride particles; carbide particles such as silicon carbide particles and boron carbide particles; diamond particles; carbonates such as calcium carbonate and barium carbonate, etc. Specific examples of organic particles include polymethyl methacrylate (PMMA) particles, poly(meth)acrylic acid particles (here (meth)acrylic acid means including acrylic acid and methacrylic acid), polyacrylonitrile particles, etc. Such abrasives can be used alone or in combination of two or more.
[0044] The technology disclosed herein can be preferably implemented in a manner that substantially only silica particles are used as abrasive particles. From such a viewpoint, it is appropriate that the proportion of silica particles in the total amount of abrasive particles is 90% by weight or more, preferably 95% by weight or more, and more preferably 98% by weight or more (e.g., 99 to 100% by weight).
[0045] <Basic compound (B)>
[0046] The grinding composition disclosed herein contains a basic compound. In this specification, a basic compound refers to a compound having a function of being dissolved in water and raising the pH of an aqueous solution. By making the grinding composition contain a basic compound, the grinding object can be efficiently ground by its chemical grinding action (alkali etching). As the basic compound, an organic or inorganic basic compound containing nitrogen, a basic compound containing phosphorus, a hydroxide of an alkali metal, a hydroxide of an alkaline earth metal, various carbonates, bicarbonates, etc. can be used. As examples of basic compounds containing nitrogen, quaternary ammonium compounds, ammonia, amines (preferably water-soluble amines) and the like can be cited. As examples of basic compounds containing phosphorus, quaternary phosphonium compounds can be cited. Such basic compounds can be used alone or in combination of two or more.
[0047] As specific examples of alkali metal hydroxides, potassium hydroxide, sodium hydroxide, etc. can be listed. As specific examples of carbonates or bicarbonates, ammonium bicarbonate, ammonium carbonate, potassium bicarbonate, potassium carbonate, sodium bicarbonate, sodium carbonate, etc. can be listed. As specific examples of amines, methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, ethylenediamine, monoethanolamine, N-(β-aminoethyl)ethanolamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, anhydrous piperazine, piperazine hexahydrate, 1-(2-aminoethyl)piperazine, N-methylpiperazine, guanidine, imidazole, triazole and other azoles can be listed. As specific examples of quaternary phosphonium compounds, quaternary phosphonium hydroxides such as tetramethylphosphonium hydroxide and tetraethylphosphonium hydroxide can be listed.
[0048] As the quaternary ammonium compound, a quaternary ammonium salt (typically a strong base) such as a tetraalkylammonium salt or a hydroxyalkyltrialkylammonium salt can be used. The anion component in the quaternary ammonium salt can be, for example, OH - 、F - , Cl - Br - ,I - 、ClO4 - 、BH4 - As examples of the above-mentioned quaternary ammonium compounds, there can be cited quaternary ammonium salts whose anions are OH-, i.e., quaternary ammonium hydroxides. As specific examples of quaternary ammonium hydroxides, there can be cited tetraalkylammonium hydroxides such as tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, tetrapentylammonium hydroxide, and tetrahexylammonium hydroxide; hydroxyalkyltrialkylammonium hydroxides such as 2-hydroxyethyltrimethylammonium hydroxide (also called choline), and the like.
[0049] Among these basic compounds, for example, at least one basic compound selected from the group consisting of alkali metal hydroxides, quaternary ammonium hydroxides and ammonia can be preferably used. Among them, tetraalkylammonium hydroxides (such as tetramethylammonium hydroxide) and ammonia are more preferred, and ammonia is particularly preferred.
[0050] <Water-soluble polymer (C)>
[0051] The polishing composition disclosed herein includes a water-soluble polymer. The water-soluble polymer can contribute to the protection of the surface of the polishing object, the improvement of the wettability of the polishing object surface after polishing, etc. The polishing composition disclosed herein is characterized in that: as a water-soluble polymer, it includes a water-soluble polymer with high performance (substrate protection) of protecting the polishing object surface from etching caused by alkali. According to the polishing composition containing a water-soluble polymer with high substrate protection, there is a tendency to reduce defects (such as LPD-N) on the polished surface.
[0052] (Modified polyvinyl alcohol polymer (C1))
[0053] In the technology disclosed herein, the polishing composition contains a modified polyvinyl alcohol polymer (hereinafter also referred to as "modified polyvinyl alcohol polymer (C1)") having an etching rate of 20 nm / hour or less. Here, in this specification, the etching rate of the modified polyvinyl alcohol polymer is determined based on the etching rate measurement specified below. The same is true in the examples described below.
[0054] [Etching rate measurement]
[0055] (1) A chemical solution LE for measuring an etching rate containing 0.175 wt % of a modified polyvinyl alcohol polymer and 0.205 wt % of ammonia, with the balance being water, was prepared.
[0056] (2) Prepare a silicon single crystal substrate (rectangular shape with a length of 6 cm, a width of 3 cm, and a thickness of 775 μm) and measure its weight W0. The silicon single crystal substrate is immersed in a cleaning solution of NH4OH (29%):H2O2 (31%):deionized water (DIW) = 2:5.3:48 (volume ratio) at 25°C for 1 minute, and then immersed in a hydrogen fluoride (HF) aqueous solution (5%) at 25°C for 30 seconds.
[0057] (3) The silicon single crystal substrate was immersed in the chemical solution LE at room temperature for 40 hours.
[0058] (4) The silicon single crystal substrate was taken out from the chemical solution LE and washed with deionized water (DIW) at 25° C. for 10 seconds.
[0059] (5) The weight W1 of the cleaned silicon single crystal substrate is measured.
[0060] (6) The etching rate [nm / hour] is calculated based on the difference between W0 and W1 and the specific gravity of the silicon single crystal substrate.
[0061] The etching rate measured based on the above-mentioned prescribed etching rate can be an indicator for evaluating the performance of the water-soluble polymer in protecting the surface of the polishing object from corrosion caused by alkali under the condition that the influence of the mechanical action of the abrasive grains is removed, which depends on the characteristics of the water-soluble polymer. When the etching rate is lower, there is a tendency to show a higher performance: the water-soluble polymer is adsorbed on the surface of the polishing object and suppresses the chemical etching of the surface by alkaline compounds, that is, the performance of protecting the surface of the polishing object.
[0062] For the reason of reducing the defect after grinding by using modified polyvinyl alcohol-based polymer (C1), it is explained without particular limitation. It is generally believed that polyvinyl alcohol-based polymer protects the substrate surface by acting on the substrate surface, and thus it is believed that it contributes to the improvement of the quality of the ground surface (specifically, reducing haze, defect). In addition, the modified polyvinyl alcohol-based polymer is compared with the non-modified polyvinyl alcohol-based polymer, and the etching rate is easy to become low (that is, the substrate protection performance is easy to become high). It is believed that in the modified polyvinyl alcohol-based polymer, particularly by using the modified polyvinyl alcohol-based polymer with an etching rate of less than 20nm / hour, the performance of protecting the surface of the grinding object becomes higher, and the defect reduction effect after grinding is further improved.
[0063] In some embodiments, the etching rate of the modified polyvinyl alcohol polymer (C1) is more preferably less than 19 nm / hour (for example, less than 18 nm / hour), and further preferably less than 17 nm / hour. The lower limit of the etching rate of the modified polyvinyl alcohol polymer is not particularly limited. From the viewpoint of increasing the grinding rate by utilizing the etching effect caused by alkali, it is appropriate that the etching rate of the modified polyvinyl alcohol polymer (C1) is generally more than 1 nm / hour, preferably more than 2 nm / hour, more preferably more than 3 nm / hour (for example, more than 4 nm / hour). From the viewpoint of increasing the grinding rate, the etching rate of the modified polyvinyl alcohol polymer (C1) can be more than 5 nm / hour, can be more than 7 nm / hour, can be more than 10 nm / hour, can be more than 12 nm / hour, or can be more than 15 nm / hour.
[0064] Here, in this specification, a polyvinyl alcohol polymer refers to a polymer containing a vinyl alcohol unit (hereinafter also referred to as a "VA unit") as its repeating unit. In addition, a modified polyvinyl alcohol polymer refers to a polymer containing a repeating unit other than a VA unit (hereinafter also referred to as a "non-VA unit") in addition to a VA unit, and refers to a polyvinyl alcohol polymer. The modified polyvinyl alcohol polymer may be a random copolymer containing a VA unit and a non-VA unit, a block copolymer, an alternating copolymer, or a graft copolymer. The modified polyvinyl alcohol polymer may contain only one non-VA unit, or may contain two or more non-VA units.
[0065] The modified polyvinyl alcohol polymer can be a polymer comprising VA units and non-VA units, wherein the non-VA units have at least one structure selected from oxyalkylene, carboxyl, (di) carboxyl, (di) carboxyl ester, phenyl, naphthyl, sulfonic, amino, hydroxyl, amide, imide, nitrile, ether, ester and their salts. In addition, as non-VA units that can be included in the modified polyvinyl alcohol polymer, for example, repeating units derived from N-vinyl monomers, N-(methyl)acryloyl monomers, repeating units derived from ethylene, repeating units derived from alkyl vinyl ethers, repeating units derived from vinyl esters of monocarboxylic acids having more than 3 carbon atoms, repeating units derived from (di) acetone compounds, etc., can be described later, but are not limited to these. As a suitable example of the above-mentioned N-vinyl monomer, N-vinyl pyrrolidone can be cited. As a suitable example of the above-mentioned N-(methyl)acryloyl monomer, N-(methyl)acryloyl morpholine can be cited. The alkyl vinyl ether may be, for example, a vinyl ether having an alkyl group having 1 to 10 carbon atoms, such as propyl vinyl ether, butyl vinyl ether, and 2-ethylhexyl vinyl ether. The vinyl ester of a monocarboxylic acid having 3 to 3 carbon atoms may be, for example, a vinyl ester of a monocarboxylic acid having 3 to 7 carbon atoms, such as vinyl propionate, vinyl butyrate, vinyl valerate, and vinyl hexanoate. Preferred examples of the (di)acetone compound include diacetone (meth)acrylamide and acetylacetone.
[0066] In some preferred embodiments, an acetalized polyvinyl alcohol polymer can be used as a modified polyvinyl alcohol polymer. As the acetalized polyvinyl alcohol polymer, for example, a polymer in which a part of the VA units contained in the polyvinyl alcohol polymer is acetalized can be listed. The modified polyvinyl alcohol polymer in which a part of the VA units contained in the above-mentioned polyvinyl alcohol polymer is acetalized (acetalized PVA (Ac-PVA)) can be obtained by reacting a part of the hydroxyl groups of the polyvinyl alcohol polymer with an aldehyde compound or a ketone compound for acetalization. Typically, the acetalized polyvinyl alcohol polymer can be obtained by an acetalization reaction of a polyvinyl alcohol polymer with an aldehyde compound. In some preferred embodiments, the carbon number of the above-mentioned aldehyde compound is 1 to 7, and more preferably 2 to 7.
[0067] Examples of the aldehyde compound include: formaldehyde; linear or branched alkyl aldehydes such as acetaldehyde, propionaldehyde, n-butyraldehyde, isobutyraldehyde, tert-butyraldehyde, and hexanal; alicyclic or aromatic aldehydes such as cyclohexanecarboxaldehyde and benzaldehyde. These may be used alone or in combination of two or more. In addition to formaldehyde, an aldehyde compound in which one or more hydrogen atoms are substituted by a halogen or the like may be used. Among these, linear or branched alkyl aldehydes are preferred from the viewpoint of high solubility in water and easy acetalization reaction, and acetaldehyde, n-propionaldehyde, n-butyraldehyde, and n-valeraldehyde are more preferred.
[0068] As the aldehyde compound, in addition to the above, aldehyde compounds having 8 or more carbon atoms, such as 2-ethylhexanal, nonanal, and decanal, can be used.
[0069] The acetalized polyvinyl alcohol polymer includes a VA unit which is a structural part represented by the following chemical formula: -CH2-CH(OH)-, and an acetalized structural unit represented by the following general formula (1) (hereinafter also referred to as a "VAC unit").
[0070]
[0071] (In formula (1), R is a hydrogen atom, or a straight-chain or branched alkyl group, which may be substituted by a functional group.)
[0072] In some preferred embodiments, R in the above formula (1) is a hydrogen atom, or a linear or branched alkyl group having 1 to 6 carbon atoms. R may be one of them, or a combination of two or more thereof. From the viewpoint of improving haze reduction performance, R is preferably a linear or branched alkyl group having 1 to 6 carbon atoms.
[0073] From the viewpoint of improving haze reduction performance, the acetalization degree of the acetalized polyvinyl alcohol polymer can be set to 1 mol% or more, can be 5 mol% or more, preferably 10 mol% or more, more preferably 15 mol% or more, further preferably 20 mol% or more, particularly preferably 25 mol% or more (e.g. 27 mol% or more). From the viewpoint of improving hydrophilicity, the acetalization degree of the acetalized polyvinyl alcohol polymer is preferably set to less than 60 mol%, further 50 mol% or less, more preferably 40 mol% or less, particularly preferably 35 mol% or less (e.g. 33 mol% or less). It should be noted that, in this specification, "acetalization degree" refers to the proportion of acetalized structural units (VAC units) in all repeating units constituting the acetalized polyvinyl alcohol polymer.
[0074] In addition, as a modified polyvinyl alcohol polymer, a cation-modified polyvinyl alcohol into which a cationic group such as a quaternary ammonium structure is introduced can also be used. As the above-mentioned cation-modified polyvinyl alcohol, for example, polyvinyl alcohol into which a cationic group derived from a monomer having a cationic group such as a diallyldialkylammonium salt, an N-(meth)acryloylaminoalkyl-N,N,N-trialkylammonium salt can be introduced can be cited. In addition, as a modified polyvinyl alcohol polymer, a non-VA unit having a chemical formula of: -CH2-CH(CR 1 (OR 4 )-CR 2 (OR 5 )-R 3 )-a polymer of the structural part shown. Here R 1 ~R3 Each independently represents a hydrogen atom or an organic group, R 4 and R 5 Each independently represents a hydrogen atom or R 6 -CO-(where R 6 For example, in the above chemical formula, R 1 ~R 3 When at least one of is an organic group, the organic group may be a linear or branched alkyl group having 1 to 8 carbon atoms. 6 The carbon number may be a linear or branched alkyl group having 1 to 8 carbon atoms.
[0075] In some embodiments, as the modified polyvinyl alcohol-based polymer, a modified polyvinyl alcohol-based polymer having a 1,2-diol structure in the side chain can be used. For example, as examples of the modified polyvinyl alcohol-based polymer, there can be cited a polymer including the R 1 ~R 5 A polymer containing non-VA units containing hydrogen atoms (butene glycol-vinyl alcohol copolymer (BVOH)).
[0076] The ratio of the molar number of VA units to the molar number of all repeating units constituting the modified polyvinyl alcohol-based polymer may be, for example, 5% or more, 10% or more, 20% or more, or 30% or more. Although not particularly limited, in some embodiments, the ratio of the molar number of the above-mentioned VA units may be 50% or more, 65% or more, 75% or more, or 80% or more. In other embodiments, the ratio of the molar number of VA units to the molar number of all repeating units constituting the modified polyvinyl alcohol-based polymer may be, for example, less than 95%, less than 90%, less than 80%, or less than 70%.
[0077] The content of VA units in the modified polyvinyl alcohol polymer (content on a weight basis) may be, for example, 5% by weight or more, 10% by weight or more, 20% by weight or more, or 30% by weight or more. Although not particularly limited, in some embodiments, the content of the VA unit may be 50% by weight or more (e.g., more than 50% by weight), 70% by weight or more, or 80% by weight or more. In some other embodiments, the content of VA units in the modified polyvinyl alcohol polymer may be, for example, less than 95% by weight, less than 90% by weight, less than 80% by weight, or less than 70% by weight.
[0078] The modified polyvinyl alcohol polymer may include multiple polymer chains with different contents of VA units in the same molecule. Here, the polymer chain refers to a part (chain segment) that constitutes a part of a molecule of polymer. For example, the modified polyvinyl alcohol polymer may include a polymer chain A with a VA unit content higher than 50% by weight and a polymer chain B with a VA unit content lower than 50% by weight (i.e., a non-VA unit content higher than 50% by weight) in the same molecule.
[0079] The polymer chain A may contain only VA units as repeating units, or may contain non-VA units in addition to VA units. The content of VA units in the polymer chain A may be 60% by weight or more, 70% by weight or more, 80% by weight or more, or 90% by weight or more. In some embodiments, the content of VA units in the polymer chain A may be 95% by weight or more, or 98% by weight or more. The repeating units constituting the polymer chain A may be substantially 100% by weight of VA units.
[0080] The polymer chain B may contain only non-VA units as repeating units, or may contain VA units in addition to non-VA units. The content of non-VA units in the polymer chain B may be 60% by weight or more, 70% by weight or more, 80% by weight or more, or 90% by weight or more. In some embodiments, the content of non-VA units in the polymer chain B may be 95% by weight or more, or 98% by weight or more. The repeating units constituting the polymer chain B may be substantially 100% by weight of non-VA units.
[0081] As examples of modified polyvinyl alcohol-based polymers containing polymer chain A and polymer chain B in the same molecule, block copolymers and graft copolymers containing these polymer chains can be cited. The above-mentioned graft copolymer can be a graft copolymer having a structure in which polymer chain B (side chain) is grafted onto polymer chain A (main chain), or a graft copolymer having a structure in which polymer chain A (side chain) is grafted onto polymer chain B (main chain). In some embodiments, a modified polyvinyl alcohol-based polymer having a structure in which polymer chain B is grafted onto polymer chain A can be used.
[0082] Examples of polymer chain B include polymer chains having repeating units derived from N-vinyl monomers as main repeating units; polymer chains having repeating units derived from N-(meth)acryloyl monomers as main repeating units; polymer chains having repeating units derived from vinyl esters of dicarboxylic acids such as fumaric acid, maleic acid, and maleic anhydride as main repeating units; polymer chains having repeating units derived from aromatic vinyl monomers such as styrene and vinylnaphthalene as main repeating units; polymer chains having oxyalkylene units as main repeating units, etc. It should be noted that in this specification, unless otherwise specified, the main repeating unit refers to a repeating unit having a content exceeding 50% by weight.
[0083] As a suitable example of polymer chain B, there can be cited a polymer chain having N-vinyl monomers as main repeating units, i.e., N-vinyl polymer chains. The content of repeating units derived from N-vinyl monomers in the N-vinyl polymer chain typically exceeds 50% by weight, and may be 70% by weight or more, 85% by weight or more, or 95% by weight or more. The polymer chain B may be substantially entirely composed of repeating units derived from N-vinyl monomers.
[0084] In this specification, examples of N-vinyl monomers include monomers having nitrogen-containing heterocycles (e.g., lactam rings), and N-vinyl chain amides. As specific examples of N-vinyl lactam monomers, N-vinyl pyrrolidone, N-vinyl piperidone, N-vinyl morpholinone, N-vinyl caprolactam, N-vinyl-1,3-oxazine-2-one, N-vinyl-3,5-morpholinedione, etc. can be cited. As specific examples of N-vinyl chain amides, N-vinyl acetamide, N-vinyl propionamide, N-vinyl butyramide, etc. can be cited. Polymer chain B, for example, can be an N-vinyl polymer chain in which more than 50% by weight (e.g., more than 70% by weight, or more than 85% by weight, or more than 95% by weight) of its repeating units are N-vinyl pyrrolidone units. The repeating units constituting polymer chain B can be substantially all N-vinyl pyrrolidone units.
[0085] As another example of polymer chain B, there can be cited a polymer chain having a repeating unit derived from an N-(meth)acryloyl type monomer as a main repeating unit, that is, an N-(meth)acryloyl polymer chain. The content of the repeating unit derived from the N-(meth)acryloyl type monomer in the N-(meth)acryloyl polymer chain typically exceeds 50% by weight, and may be 70% by weight or more, 85% by weight or more, or 95% by weight or more. The polymer chain B may be substantially entirely composed of repeating units derived from N-(meth)acryloyl type monomers.
[0086] In the present specification, examples of N-(meth)acryloyl-type monomers include chain amides having N-(meth)acryloyl groups and cyclic amides having N-(meth)acryloyl groups. Examples of chain amides having N-(meth)acryloyl groups include (meth)acrylamide; N-alkyl(meth)acrylamide such as N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, N-propyl(meth)acrylamide, N-isopropyl(meth)acrylamide, and N-n-butyl(meth)acrylamide; and N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dipropyl(meth)acrylamide, N,N-diisopropyl(meth)acrylamide, and N,N-di(n-butyl)(meth)acrylamide. Examples of the cyclic amide having an N-(meth)acryloyl group include N-(meth)acryloylmorpholine and N-(meth)acryloylpyrrolidine.
[0087] As another example of polymer chain B, there can be mentioned a polymer chain containing an oxyalkylene unit as a main repeating unit, that is, an oxyalkylene polymer chain. The content of the oxyalkylene unit in the oxyalkylene polymer chain is typically more than 50% by weight, and may be 70% by weight or more, 85% by weight or more, or 95% by weight or more. The repeating units contained in polymer chain B may be substantially all oxyalkylene units.
[0088] Examples of oxyalkylene units include oxyethylene units, oxypropylene units, oxybutylene units, etc. Such oxyalkylene units may be repeating units derived from corresponding alkylene oxides, respectively. The oxyalkylene units contained in the oxyalkylene polymer chain may be one or more than two. For example, it may be an oxyalkylene polymer chain comprising a combination of oxyethylene units and oxypropylene units. In the oxyalkylene polymer chain comprising more than two oxyalkylene units, these oxyalkylene units may be random copolymers of corresponding alkylene oxides, may be block copolymers, may be alternating copolymers, or graft copolymers.
[0089] As other examples of the polymer chain B, there can be listed a polymer chain comprising repeating units derived from an alkyl vinyl ether (e.g., a vinyl ether having an alkyl group having 1 to 10 carbon atoms), a polymer chain comprising repeating units derived from a monocarboxylic acid vinyl ester (e.g., a vinyl ester of a monocarboxylic acid having 3 or more carbon atoms), a polymer chain into which a cationic group (e.g., a cationic group having a quaternary ammonium structure) is introduced, and the like.
[0090] In some embodiments, the degree of saponification of the modified polyvinyl alcohol-based polymer is 50 mol % or more, preferably 65 mol % or more, more preferably 70 mol % or more, for example 75 mol % or more.
[0091] In the technology disclosed herein, the polishing composition includes a modified polyvinyl alcohol polymer (modified polyvinyl alcohol polymer (C1)) having an etching rate of 20 nm / hour or less in the above-mentioned modified polyvinyl alcohol polymer. The etching rate of the water-soluble polymer can be adjusted by controlling the structure of the constituent units of the water-soluble polymer (for example, the structure of the non-VA unit in the modified polyvinyl alcohol polymer), the constituent ratio (for example, the ratio of the non-VA unit in the modified polyvinyl alcohol polymer), the molecular weight, etc. As modified polyvinyl alcohol polymers having an etching rate of 20 nm / hour or less, acetalized polyvinyl alcohol polymers, polyvinyl alcohol polymers containing repeating units derived from alkyl vinyl ethers, etc. can be listed, but are not limited to these. The modified polyvinyl alcohol polymer (C1) can be used alone or in combination of two or more.
[0092] In some embodiments, the weight average molecular weight (Mw) of the modified polyvinyl alcohol-based polymer (C1) can be set to, for example, 100×10 4 Below, 60×10 4 The following are appropriate. From the viewpoint of concentration efficiency, etc., the above Mw can be 30×10 4 Below, preferably 20×10 4 Below, for example, it can be 10×10 4 Below, can be 8×10 4 Below, can be 5×10 4 Below, it can also be 3×10 4 As the Mw of the modified polyvinyl alcohol polymer (C1) decreases, the dispersion stability of the modified polyvinyl alcohol polymer (C1) tends to improve. In addition, from the viewpoint of appropriately protecting the polished surface and maintaining or improving the surface quality, the Mw may be, for example, 0.2×10 4 Above, usually preferably 0.3×10 4 As the Mw of the modified polyvinyl alcohol polymer (C1) increases, the effect of improving the protection and wettability of the polishing object tends to increase. From this point of view, in some embodiments, the Mw is 0.5×10 4 The above is appropriate, preferably 0.8×10 4 above.
[0093] As the Mw of the water-soluble polymer, the molecular weight calculated from the value (water system, polyethylene oxide conversion) based on the aqueous gel permeation chromatography (GPC) can be used. The same is true for the Mw of the modified polyvinyl alcohol polymer (C1) and the water-soluble polymer (C2) described later. As a GPC measuring device, the model name "HLC-8320GPC" manufactured by Tosoh Corporation can be used. The measurement can be carried out, for example, according to the following conditions. The same method is also used for the examples described later.
[0094] [GPC measurement conditions]
[0095] Sample concentration: 0.1 wt%
[0096] Column: TSKgel GMPW XL
[0097] Detector: Differential Refractometer
[0098] Eluent: 100 mM sodium nitrate aqueous solution
[0099] Flow rate: 1mL / min
[0100] Measurement temperature: 40℃
[0101] Sample injection volume: 200 μL
[0102] Although not particularly limited, in some embodiments, the content of the modified polyvinyl alcohol polymer (C1) in the polishing composition can be set to, for example, 0.01 parts by weight or more relative to 100 parts by weight of abrasive (typically silica particles). From the perspective of reducing defects, it is appropriate to set it to 0.1 parts by weight or more, preferably 0.5 parts by weight or more, more preferably 1 part by weight or more, and it can be 1.5 parts by weight or more, 2 parts by weight or more, 3 parts by weight or more, or 3.5 parts by weight or more. The content of the modified polyvinyl alcohol polymer (C1) relative to 100 parts by weight of abrasive can be, for example, 50 parts by weight or less, or 30 parts by weight or less. From the perspective of the dispersion stability of the polishing composition, in some embodiments, it is appropriate to set the content of the modified polyvinyl alcohol polymer (C1) relative to 100 parts by weight of abrasive to 15 parts by weight or less, preferably 10 parts by weight or less, more preferably 5 parts by weight or less, and it can be less than 3 parts by weight, 2.5 parts by weight or less, or 2 parts by weight or less. By appropriately setting the amount of the modified polyvinyl alcohol polymer (C1) to be used within the above range, high surface quality after polishing can be achieved.
[0103] (Water-soluble polymer (C2))
[0104] The polishing composition disclosed herein may further include a second water-soluble polymer (hereinafter, also referred to as "water-soluble polymer (C2)") having a chemical structure different from that of the modified polyvinyl alcohol polymer (C1) in addition to the modified polyvinyl alcohol polymer (C1). By using the water-soluble polymer (C2) together with the modified polyvinyl alcohol polymer (C1), it is expected that the polishing rate will be improved, the surface quality after polishing will be improved, and the like. As the water-soluble polymer (C2), there is no particular limitation, and various water-soluble polymers can be used. The water-soluble polymer (C2) can be used alone or in combination of two or more.
[0105] As water-soluble polymers (C2), compounds containing hydroxyl groups, carboxyl groups, acyloxy groups, sulfonic groups, amide structures, imide structures, quaternary ammonium structures, heterocyclic structures, vinyl structures, etc. in the molecule can be cited. As water-soluble polymers (C2), for example, cellulose derivatives, starch derivatives, polymers containing oxyalkylene units, polyvinyl alcohol polymers (wherein, the above-mentioned modified polyvinyl alcohol polymers (C1) are excluded), polymers containing nitrogen atoms, polymers containing (meth) acrylic acid units, etc. can be used. As one form of polymers containing nitrogen atoms, N-vinyl polymers, N-(meth)acryloyl polymers, etc. can be used. The water-soluble polymer (C2) can be a polymer derived from natural products or a synthetic polymer.
[0106] In some embodiments, a polymer derived from natural products is used as the water-soluble polymer (C2). Examples of the polymer derived from natural products include cellulose derivatives and starch derivatives.
[0107] In some embodiments, a cellulose derivative is used as the water-soluble polymer (C2). Here, the cellulose derivative is a polymer containing a β-glucose unit as a main repeating unit. Specific examples of cellulose derivatives include hydroxyethyl cellulose (HEC), hydroxypropyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, ethyl cellulose, ethyl hydroxyethyl cellulose, carboxymethyl cellulose, etc. Among them, HEC is preferred.
[0108] In some other embodiments, a starch derivative is used as the water-soluble polymer (C2). The starch derivative is a polymer containing an α-glucose unit as a main repeating unit, and examples thereof include α-starch, pullulan, carboxymethyl starch, and cyclodextrin.
[0109] In some other preferred embodiments, a synthetic polymer is used as the water-soluble polymer (C2). The surface quality improvement effect disclosed herein can be preferably exerted in the embodiment using a synthetic polymer as the water-soluble polymer (C2).
[0110] In some ways, as water-soluble polymer (C2), a polymer comprising an oxyalkylene unit is used. As a polymer comprising an oxyalkylene unit, block copolymers of polyethylene oxide (PEO), ethylene oxide (EO) and propylene oxide (PO) or butylene oxide (BO), random copolymers of EO and PO or BO, etc. can be exemplified. Among them, preferably a block copolymer of EO and PO or a random copolymer of EO and PO. The block copolymer of EO and PO can be a diblock copolymer or a triblock copolymer comprising a PEO block and a polypropylene oxide (PPO) block, etc. The example of the above-mentioned triblock copolymer includes a PEO-PPO-PEO type triblock copolymer and a PPO-PEO-PPO type triblock copolymer. Usually, more preferably a PEO-PPO-PEO type triblock copolymer.
[0111] It should be noted that, in the present specification, unless otherwise specified, the term "copolymer" means various copolymers including random copolymers, alternating copolymers, block copolymers, graft copolymers, and the like.
[0112] In the block copolymer or random copolymer of EO and PO, from the viewpoint of solubility in water, washability, etc., the molar ratio of EO to PO constituting the copolymer (EO / PO) is preferably greater than 1, more preferably 2 or more, and further preferably 3 or more (e.g. 5 or more).
[0113] In some embodiments, as a water-soluble polymer (C2), a polyvinyl alcohol-based polymer (except the modified polyvinyl alcohol-based polymer (C1)) can be used. As such a polyvinyl alcohol-based polymer, an unmodified polyvinyl alcohol (unmodified PVA) containing only VA units as repeating units is exemplified. The saponification degree of the unmodified PVA can be, for example, 60% or more, and from the perspective of water solubility, can be 70% or more, 80% or more, or 90% or more. In some embodiments, the saponification degree of the unmodified PVA can be 98% or more (completely saponified).
[0114] In some embodiments, as a water-soluble polymer (C2), an N-vinyl polymer can be used. Examples of N-vinyl polymers include polymers comprising repeating units derived from monomers having nitrogen-containing heterocycles (e.g., lactam rings). Examples of such polymers include homopolymers and copolymers of N-vinyl lactam monomers (e.g., copolymers having a copolymerization ratio of more than 50% by weight of N-vinyl lactam monomers), homopolymers and copolymers of N-vinyl chain amides (e.g., copolymers having a copolymerization ratio of more than 50% by weight of N-vinyl chain amides), etc.
[0115] Specific examples of N-vinyl lactam monomers (i.e., compounds having a lactam structure and an N-vinyl group in one molecule) include N-vinyl pyrrolidone (VP), N-vinyl piperidone, N-vinyl morpholinone, N-vinyl caprolactam (VC), N-vinyl-1,3-oxazine-2-one, N-vinyl-3,5-morpholinedione, etc. Specific examples of polymers containing N-vinyl lactam monomer units include polyvinyl pyrrolidone, polyvinyl caprolactam, random copolymers of VP and VC, random copolymers of one or both of VP and VC and other vinyl monomers (e.g., acrylic monomers, vinyl ester monomers, etc.), block copolymers containing polymer chains containing one or both of VP and VC, alternating copolymers, graft copolymers, etc.
[0116] Specific examples of the N-vinyl chain amide include N-vinylacetamide, N-vinylpropionamide, and N-vinylbutyramide.
[0117] In some other embodiments, as the water-soluble polymer (C2), an N-(meth)acryloyl type polymer can be used. Examples of N-(meth)acryloyl type polymers include homopolymers and copolymers of N-(meth)acryloyl type monomers (typically copolymers in which the copolymerization ratio of N-(meth)acryloyl type monomers exceeds 50 weight %). Examples of N-(meth)acryloyl type monomers include chain amides having N-(meth)acryloyl groups and cyclic amides having N-(meth)acryloyl groups. It should be noted that, in this specification, (meth)acryloyl type refers to a meaning including acryl type and methacryloyl type. In addition, in this specification, (meth)acryloyl refers to a meaning including acryl group and methacryloyl group.
[0118] Examples of chain amides having N-(meth)acryloyl groups include (meth)acrylamide; N-alkyl(meth)acrylamide such as N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, N-propyl(meth)acrylamide, N-isopropyl(meth)acrylamide, and N-n-butyl(meth)acrylamide; and N,N-dialkyl(meth)acrylamide such as N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dipropyl(meth)acrylamide, N,N-diisopropyl(meth)acrylamide, and N,N-di(n-butyl)(meth)acrylamide. In addition, for example, N-hydroxyethylacrylamide (HEAA) can be cited. Examples of polymers containing chain amides having N-(meth)acryloyl groups as monomer units include homopolymers of N-isopropylacrylamide and copolymers of N-isopropylacrylamide (e.g., copolymers in which the copolymerization ratio of N-isopropylacrylamide exceeds 50% by weight). It should be noted that, in the present specification, (meth)acrylamide means including acrylamide and methacrylamide.
[0119] As examples of cyclic amides with N-(meth)acryloyl groups, N-acryloyl morpholine, N-acryloyl thiomorpholine, N-acryloyl piperidine, N-acryloyl pyrrolidine, N-methacryloyl morpholine, N-methacryloyl piperidine, N-methacryloyl pyrrolidine, etc. can be cited. As examples of polymers containing cyclic amides with N-(meth)acryloyl groups as monomer units, acryloyl morpholine polymers (PACMO) can be cited. As typical examples of acryloyl morpholine polymers, homopolymers of N-acryloyl morpholine (ACMO) and copolymers of ACMO (e.g., copolymers with a copolymerization ratio of ACMO exceeding 50% by weight) can be cited. In acryloyl morpholine polymers, the proportion of the number of moles of ACMO units in the number of moles of all repeating units is usually 50% or more, and it is appropriate to be 80% or more (e.g., 90% or more, typically 95% or more). The water-soluble polymer (C2) may have all repeating units substantially composed of ACMO units.
[0120] In some embodiments, as a water-soluble polymer (C2), a carboxylic acid polymer is used. As examples of carboxylic acid polymers, polymers comprising maleic acid units, polymers comprising (meth) acrylic acid units, etc. can be listed. As examples of polymers comprising maleic acid units, styrene-maleic acid copolymers or their salts, styrene-maleic anhydride copolymers, styrene sulfonic acid-maleic acid copolymers or their salts, copolymers of styrene sulfonates and maleic acid, maleic acid-vinyl acetate copolymers, etc. can be listed. As examples of polymers comprising (meth) acrylic acid units, polyacrylic acid or their salts, styrene-acrylic acid copolymers or their salts, styrene sulfonic acid-acrylic acid copolymers or their salts, copolymers of styrene sulfonates and acrylic acid, acrylic acid-vinyl acetate copolymers, acrylic acid / sulfonic acid monomer copolymers, etc. can be listed. It should be noted that in this specification, (meth) acrylic acid refers to the meaning including acrylic acid and methacrylic acid.
[0121] When the water-soluble polymer (C2) is a polymer containing a chain amide having an N-(meth)acryloyl group as a monomer unit, the Mw of the water-soluble polymer (C2) can be, for example, 100×10 4 Below, 50×10 4 The following are appropriate. From the perspective of concentration efficiency, etc., the above Mw can be 30×10 4 Below, can be 10×10 4 Below, can be 8×10 4 Below, can also be 6×10 4 From the viewpoint of improving the surface quality, the Mw may be, for example, 1×10 4 Above, can be 2×10 4 Above, it can also be 3×10 4 More than (for example, 4×10 4 By using a second water-soluble polymer having a high Mw, a high surface quality can be easily obtained.
[0122] When the water-soluble polymer (C2) is a polymer containing a cyclic amide having an N-(meth)acryloyl group as a monomer unit, the Mw of the water-soluble polymer (C2) can be, for example, 100×10 4 Below, 70×10 4 The following are appropriate. From the perspective of concentration efficiency, etc., the above Mw can be 60×10 4 Below, can be 50×10 4 Below, can be 35×10 4 Below, can be less than 35×10 4 , can be 30×10 4 Below, can be 20×10 4From the viewpoint of improving the surface quality, the Mw may be, for example, 1.0×10 4 Above, can be 5×10 4 Above, can be 10×10 4 Above, can be 15×10 4 Above, can be 20×10 4 Above, can be 25×10 4 More than (e.g. more than 25×10 4 ). By using a water-soluble polymer (C2) having a high Mw, a high surface quality can be easily obtained.
[0123] When the water-soluble polymer (C2) is a polymer containing a (meth)acrylic acid unit, the Mw of the water-soluble polymer (C2) can be, for example, 800×10 4 Below, 500×10 4 The following are appropriate. From the viewpoint of concentration efficiency, etc., the above Mw can be 300×10 4 Below, preferably 200×10 4 Below, for example, it can be 175×10 4 Below, can be 150×10 4 Below, can also be 140×10 4 In addition, from the viewpoint of appropriately protecting the polished surface and maintaining or improving the surface quality, the Mw may be, for example, 20×10 4 Above, can be 50×10 4 Above, it can also be 100×10 4 Above (for example, 130×10 4 By using a water-soluble polymer (C2) having a high Mw, a high surface quality can be easily obtained.
[0124] When the water-soluble polymer (C2) is a polymer containing an oxyalkylene unit, the Mw of the water-soluble polymer (C2) can be set to 10×10 4 Below, can be 5×10 4 Below, can be 3×10 4 Below, it can also be 2×10 4 The above Mw can be set to 5×10 4 Above, it can be 1×10 4 Above, it can be 1.2×10 4 Above, it can also be 1.5×10 4 above.
[0125] Although not particularly limited, in some embodiments, as the above-mentioned water-soluble polymer (C2), a water-soluble polymer (C2) having a higher Mw than the Mw of the modified polyvinyl alcohol-based polymer (C1) is preferably used. For example, the ratio of the Mw of the water-soluble polymer (C2) to the Mw of the modified polyvinyl alcohol-based polymer (C1) is preferably greater than 1, and can be 1.1 or more, 1.3 or more, 1.5 or more, 1.8 or more, 2 or more, 3 or more, 5 or more, 10 or more, 15 or more, 20 or more, 30 or more, or 50 or more. For example, the ratio of the Mw of the water-soluble polymer (C2) to the Mw of the modified polyvinyl alcohol-based polymer (C1) can be 300 or less, 250 or less, 200 or less, 150 or less, or 100 or less. By using the Mw of two water-soluble polymers having the above-mentioned relative Mw, it is preferably possible to achieve a high surface quality after polishing.
[0126] Although not particularly limited, in some embodiments, the content of the water-soluble polymer (C2) in the grinding composition can be set to 0.01 parts by weight or more relative to 100 parts by weight of abrasive (typically silica particles). From the viewpoint of reducing haze, it is appropriate to set it to 0.1 parts by weight or more, preferably 0.5 parts by weight or more, more preferably 1 part by weight or more, and it can also be 2 parts by weight or more. In addition, the content of the water-soluble polymer (C2) relative to 100 parts by weight of abrasive can be, for example, 50 parts by weight or less, or 30 parts by weight or less. From the viewpoint of the dispersion stability of the grinding composition, in some embodiments, it is appropriate to set the content of the water-soluble polymer (C2) relative to 100 parts by weight of abrasive to 15 parts by weight or less, preferably 10 parts by weight or less, more preferably 5 parts by weight or less, for example, 3.5 parts by weight or less. By appropriately setting the amount of the water-soluble polymer (C2) used according to the above range, a high surface quality can be obtained.
[0127] Although not particularly limited, in some embodiments, the total content of the water-soluble polymer contained in the grinding composition can be set to 0.01 parts by weight or more relative to 100 parts by weight of abrasive grains (typically silica particles). From the viewpoint of improving the surface quality, it is appropriate to set it to 0.1 parts by weight or more, preferably 0.5 parts by weight or more, more preferably 1 part by weight or more, further preferably 2 parts by weight or more, particularly preferably 4 parts by weight or more, and it can also be 6 parts by weight or more. In addition, relative to 100 parts by weight of abrasive grains, the total content of the above-mentioned water-soluble polymers can be, for example, 50 parts by weight or less, or 30 parts by weight or less. From the viewpoint of the dispersion stability of the grinding composition, in some embodiments, relative to 100 parts by weight of abrasive grains, the total content of the above-mentioned water-soluble polymers is set to 15 parts by weight or less, preferably 12 parts by weight or less, and it can also be 10 parts by weight or less (for example, less than 10 parts by weight).
[0128] Although not particularly limited, in some embodiments, the ratio (W2 / W1) of the content W2 of the water-soluble polymer (C2) to the content W1 of the modified polyvinyl alcohol-based polymer (C1) is, for example, 0.01 or more on a weight basis, 0.1 or more is appropriate, preferably 0.2 or more, 0.4 or more, 0.6 or more, or 0.8 or more. In addition, the upper limit of the above ratio (W2 / W1) is, for example, 10 or less on a weight basis, 5 or less is appropriate, preferably 3 or less, more preferably less than 2, or 1 or less (less than 1). By appropriately setting the above ratio (W2 / W1) within the above range, the effect produced by the technology disclosed herein can be preferably exerted.
[0129] <Chelating agent (D)>
[0130] The grinding composition disclosed herein is characterized in that it contains a chelating agent. Generally, the chelating agent forms a complex by capturing the metal impurity components in the grinding composition, thereby suppressing metal pollution and helping to reduce the defects caused by metal pollution. If such a chelating agent is used together with a modified polyvinyl alcohol-based polymer (C1) with high surface protectiveness of the grinding object and the silica particles as abrasive particles, in addition to reducing the defects of the grinding surface, there is also a tendency to increase the grinding rate. In the technology disclosed herein, as a reason for increasing the grinding rate by adding a chelating agent, it is not particularly limited, and it is believed that the chelating agent plays a role in attracting the silica particles to the surface of the grinding object, thereby increasing the frequency of action of the silica particles on the grinding surface, which helps to increase the grinding rate.
[0131] Examples of chelating agents include aminocarboxylic acid chelating agents and organic phosphonic acid chelating agents. Specific examples of aminocarboxylic acid chelating agents include alanine, glycine, ethylenediaminetetraacetic acid, sodium ethylenediaminetetraacetate, nitrilotriacetic acid, sodium nitrilotriacetate, ammonium nitrilotriacetate, hydroxyethylethylenediaminetriacetic acid, sodium hydroxyethylethylenediaminetriacetate, diethylenetriaminepentaacetic acid, sodium diethylenetriaminepentaacetate, triethylenetetraaminehexaacetic acid, sodium triethylenetetraaminehexaacetate, and trans-1,2-cyclohexanediaminetetraacetic acid. Specific examples of the organic phosphonic acid chelating agent include 2-aminoethylphosphonic acid, 1-hydroxyethylidene-1,1-diphosphonic acid, aminotri(methylenephosphonic acid), ethylenediaminetetra(methylenephosphonic acid), diethylenetriaminepenta(methylenephosphonic acid), ethane-1,1-diphosphonic acid, ethane-1,1,2-triphosphonic acid, ethane-1-hydroxy-1,1-diphosphonic acid, ethane-1-hydroxy-1,1,2-triphosphonic acid, ethane-1,2-dicarboxy-1,2-diphosphonic acid, methanehydroxyphosphonic acid, 2-phosphonobutane-1,2-dicarboxylic acid, phosphonobutanetricarboxylic acid (PBTC), nitrilotri(methylenephosphonic acid) (NTMP), and α-methylphosphonosuccinic acid. Among these chelating agents, ethylenediaminetetraacetic acid, diethylenetriaminepentaacetic acid, triethylenetetraaminehexaacetic acid, ethylenediaminetetra(methylenephosphonic acid), diethylenetriaminepenta(methylenephosphonic acid), and trans-1,2-cyclohexanediaminetetraacetic acid are preferred, and ethylenediaminetetra(methylenephosphonic acid), triethylenetetraaminehexaacetic acid, and trans-1,2-cyclohexanediaminetetraacetic acid are more preferred. The chelating agents may be used alone or in combination of two or more.
[0132] Although not particularly limited, in some ways, relative to 100 parts by weight of abrasive (typically silica particles), the content of the chelating agent in the grinding composition can be set to, for example, 0.01 parts by weight or more. From the viewpoint of reducing the defects caused by metal pollution, it is appropriate to set it to 0.1 parts by weight or more, preferably 0.5 parts by weight or more, more preferably 1 part by weight or more, or 2 parts by weight or more. In addition, the content of the chelating agent relative to 100 parts by weight of abrasive can be, for example, less than 20 parts by weight, or less than 10 parts by weight. From the viewpoint of the dispersion stability of the grinding composition, in some ways, it is appropriate to set the content of the chelating agent relative to 100 parts by weight of abrasive to less than 7 parts by weight, preferably less than 5 parts by weight, more preferably less than 3 parts by weight, for example, less than 2.5 parts by weight. By appropriately setting the usage amount of the chelating agent to the above range, high surface quality can be obtained.
[0133] <Surfactant (E)>
[0134] In some embodiments, the polishing composition preferably includes at least one surfactant. By making the polishing composition contain a surfactant, the haze of the polished surface can be reduced. According to the technology disclosed herein, by including the combination of the above-mentioned water-soluble polymer and the composition of the surfactant, the quality of the polished surface can be further improved. As a surfactant, anionic, cationic, nonionic, and amphoteric surfactants can be used. Generally, anionic or nonionic surfactants can be preferably used. From the perspective of low foaming and ease of pH adjustment, nonionic surfactants are more preferred. For example, oxyalkylene polymers such as polyethylene glycol, polypropylene glycol, and polytetramethylene glycol; polyoxyalkylene derivatives (such as polyoxyalkylene adducts) such as polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene alkylamines, polyoxyethylene fatty acid esters, polyoxyethylene glycerol ether fatty acid esters, and polyoxyethylene sorbitan fatty acid esters; copolymers of various oxyalkylenes (such as diblock copolymers, triblock copolymers, random copolymers, alternating copolymers) and other nonionic surfactants. The surfactant may be used alone or in combination of two or more.
[0135] Specific examples of the nonionic surfactant include block copolymers of ethylene oxide (EO) and propylene oxide (PO) (diblock copolymers, PEO (polyethylene oxide) -PPO (polypropylene oxide) -PEO type triblocks, PPO-PEO-PPO type triblock copolymers, etc.), random copolymers of EO and PO, polyoxyethylene glycol, polyoxyethylene propyl ether, polyoxyethylene butyl ether, polyoxyethylene pentyl ether, polyoxyethylene hexyl ether, polyoxyethylene octyl ether, polyoxyethylene-2-ethylhexyl ether, polyoxyethylene nonyl ether, polyoxyethylene decyl ether, polyoxyethylene isodecyl ether, polyoxyethylene tridecyl ether, polyoxyethylene lauryl ether, polyoxyethylene cetyl ether, polyoxyethylene stearyl ether, polyoxyethylene isostearyl ether, polyoxyethylene Ethyl oleyl ether, polyoxyethylene phenyl ether, polyoxyethylene octyl phenyl ether, polyoxyethylene nonyl phenyl ether, polyoxyethylene dodecyl phenyl ether, polyoxyethylene styrenated phenyl ether, polyoxyethylene laurylamine, polyoxyethylene stearylamine, polyoxyethylene oleylamine, polyoxyethylene monolaurate, polyoxyethylene monostearate, polyoxyethylene distearate, polyoxyethylene monooleate, polyoxyethylene dioleate, polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan trioleate, polyoxyethylene sorbitan tetraoleate, polyoxyethylene castor oil, polyoxyethylene hydrogenated castor oil, etc. Among them, as preferred surfactants, block copolymers of EO and PO (especially PEO-PPO-PEO type triblock copolymers), random copolymers of EO and PO, and polyoxyethylene alkyl ethers (e.g., polyoxyethylene decyl ether) can be listed. As polyoxyethylene alkyl ethers, polyoxyethylene alkyl ethers having an EO addition molar number of about 1 to 10 (e.g., about 3 to 8) are preferably used.
[0136] In some embodiments, it is preferable to use a nonionic surfactant. The use of a nonionic surfactant tends to further improve the haze reduction performance.
[0137] The molecular weight of the surfactant is, for example, less than 5000, and from the viewpoints of filterability, cleanability, etc., it is preferably less than 4500, for example, it can be less than 4000. In addition, from the viewpoints of surface activity, it is appropriate that the molecular weight of the surfactant is usually more than 200, and from the viewpoints of haze reduction effect, it is preferably more than 250 (for example, more than 300). The more preferred range of the molecular weight of the surfactant may also be different according to the type of the surfactant. For example, when polyoxyethylene alkyl ether is used as a surfactant, its molecular weight is, for example, preferably less than 2000, more preferably less than 1900 (for example, less than 1800), further preferably less than 1500, and can also be less than 1000 (for example, less than 500). In addition, for example, when a block copolymer of EO and PO is used as a surfactant, its weight-average molecular weight can be, for example, more than 500, more than 1000, more than 1500, more than 2000, or more than 2500. The upper limit of the weight average molecular weight is, for example, less than 5000, preferably 4500 or less, for example, less than 4000, less than 3800, or less than 3500.
[0138] As the molecular weight of the surfactant, the molecular weight calculated by the chemical formula can be adopted, or the value of the weight average molecular weight sought to be achieved by GPC (water system, polyethylene glycol conversion) can be adopted. About the measurement conditions of GPC, the measurement conditions identical with the above-mentioned water-soluble polymer can be adopted. For example, in the case of polyoxyethylene alkyl ether, it is preferred to adopt the molecular weight calculated by the chemical formula, and in the case of the block copolymer of EO and PO, it is preferred to adopt the weight average molecular weight sought to be achieved by the above-mentioned GPC.
[0139] Although not particularly limited, in the case where the polishing composition includes a surfactant, from the viewpoint of cleaning properties, it is usually appropriate to set the content of the surfactant to 20 parts by weight or less, preferably 10 parts by weight or less, and more preferably 6 parts by weight or less (e.g., 3 parts by weight or less) relative to 100 parts by weight of abrasive grains (typically silica grains). From the viewpoint of better exerting the effect of the use of the surfactant, it is appropriate to set the content of the surfactant to 0.001 parts by weight or more, preferably 0.01 parts by weight or more, more preferably 0.1 parts by weight or more, and may be 0.5 parts by weight or more relative to 100 parts by weight of abrasive grains.
[0140] <Water>
[0141] The polishing composition disclosed herein typically contains water. As the water contained in the polishing composition, ion exchange water (deionized water), pure water, ultrapure water, distilled water, etc. can be preferably used. In order to avoid the effects of other components contained in the polishing composition being inhibited as much as possible, the water used, for example, preferably has a total content of transition metal ions below 100 ppb. For example, the purity of water can be improved by removing impurity ions using ion exchange resins, removing foreign matter using filters, and distillation. It should be noted that the polishing composition disclosed herein can also further contain an organic solvent (lower alcohol, lower ketone, etc.) that can be uniformly mixed with water as needed. Preferably, 90% by volume or more of the solvent contained in the polishing composition is water, and more preferably 95% by volume or more (for example, 99 to 100% by volume) is water.
[0142] <Other ingredients>
[0143] The polishing composition disclosed herein may further contain known additives that can be used in polishing compositions (e.g., polishing compositions used in the fine polishing process of silicon wafers), such as organic acids (except the above-mentioned chelating agent (D)), organic acid salts (except the above-mentioned chelating agent (D)), inorganic acids, inorganic acid salts, chelating agents, preservatives, and mildew inhibitors, as needed, within the range that does not significantly hinder the effects of the present invention.
[0144] Organic acids and salts thereof, and inorganic acids and salts thereof can be used alone or in combination of two or more. Examples of organic acids include fatty acids such as formic acid, acetic acid, propionic acid, aromatic carboxylic acids such as benzoic acid, phthalic acid, itaconic acid, citric acid, oxalic acid, tartaric acid, malic acid, maleic acid, fumaric acid, succinic acid, glycolic acid, malonic acid, gluconic acid, lactic acid, organic sulfonic acids such as methanesulfonic acid, etc. Examples of organic acid salts include alkali metal salts (sodium salts, potassium salts, etc.) and ammonium salts of organic acids. Examples of inorganic acids include hydrochloric acid, phosphoric acid, sulfuric acid, phosphonic acid, nitric acid, phosphinic acid, boric acid, carbonic acid, etc. Examples of inorganic acid salts include alkali metal salts (sodium salts, potassium salts, etc.) and ammonium salts of inorganic acids.
[0145] The grinding composition disclosed herein is preferably substantially free of oxidant. This is because, when the grinding composition includes an oxidant, the grinding composition is supplied to a substrate (such as a silicon wafer), so that the surface of the substrate is oxidized to produce an oxide film, and the grinding rate may be reduced. As a specific example of the oxidant mentioned here, hydrogen peroxide (H2O2), sodium persulfate, ammonium persulfate, sodium dichloroisocyanurate, etc. can be listed. It should be noted that the grinding composition substantially does not contain an oxidant, which means that at least it does not intentionally contain an oxidant. Therefore, the grinding composition that inevitably contains a trace amount of oxidant (for example, the molar concentration of the oxidant in the grinding composition is 0.001 mol / L or less, preferably 0.0005 mol / L or less, more preferably 0.0001 mol / L or less, further preferably 0.00005 mol / L or less, particularly preferably 0.00001 mol / L or less) due to raw materials, preparation methods, etc. can be included in the concept of the grinding composition substantially free of oxidant mentioned here.
[0146] <pH>
[0147] The pH of the polishing composition disclosed herein is not particularly limited, and an appropriate pH can be adopted according to the substrate, etc. In some embodiments, the pH of the polishing composition is appropriately 8.0 or more, preferably 8.5 or more, and more preferably 9.0 or more. If the pH of the polishing composition becomes high, there is a tendency for the polishing rate to increase. On the other hand, from the viewpoint of preventing the dissolution of the silica particles and suppressing the reduction of the mechanical polishing effect, the pH of the polishing composition is usually appropriately 12.0 or less, preferably 11.0 or less, more preferably 10.8 or less, and further preferably 10.5 or less.
[0148] It should be noted that in the technology disclosed herein, the pH of the polishing composition can be determined as follows: using a pH meter (e.g., a glass electrode hydrogen ion concentration indicator (model F-72) manufactured by Horiba, Ltd.), after performing a three-point calibration using a standard buffer solution (phthalate pH buffer solution pH: 4.01 (25°C), neutral phosphate pH buffer solution pH: 6.86 (25°C), carbonate pH buffer solution pH: 10.01 (25°C)), the glass electrode is inserted into the composition to be measured, and the value after stabilization for more than 2 minutes is measured.
[0149] <Polishing fluid>
[0150] The grinding composition disclosed herein is typically supplied to the surface of the substrate in the form of a grinding liquid comprising the grinding composition, and is used for the grinding of the substrate. The above-mentioned grinding liquid can be, for example, a grinding liquid prepared by diluting any grinding composition disclosed herein (typically diluted with water). Alternatively, the grinding composition can also be used directly as a grinding liquid. As other examples of the grinding liquid comprising the grinding composition disclosed herein, a grinding liquid formed by adjusting the pH of the composition can be listed.
[0151] The content of abrasive grains (typically silica particles) in the polishing liquid is not particularly limited, for example, 0.005% by weight or more, preferably 0.01% by weight or more, more preferably 0.03% by weight or more, and further preferably 0.06% by weight or more. With the increase of the content of abrasive grains, a higher polishing rate can be achieved. It is appropriate that the above content is 10% by weight or less, preferably 7% by weight or less, more preferably 5% by weight or less, and further preferably 2% by weight or less, for example, 1% by weight or less, 0.5% by weight or less, or 0.4% by weight or less. Thus, it is easy to maintain the surface quality.
[0152] The content of the alkaline compound in the polishing liquid is not particularly limited. From the viewpoints of improving the polishing rate, it is usually appropriate to set the above content to more than 0.0005 weight %, preferably to more than 0.001 weight %, and further preferably to more than 0.003 weight %. In addition, from the viewpoints of improving the surface quality (for example, reducing the haze), it is appropriate to set the above content to less than 0.1 weight %, preferably to less than 0.05 weight %, and more preferably to less than 0.03 weight % (for example, less than 0.025 weight %, further less than 0.01 weight %).
[0153] Although not particularly limited, in some embodiments, from the viewpoint of improving the surface quality, the content of the modified polyvinyl alcohol polymer (C1) in the polishing liquid can be, for example, 0.0001% by weight or more, and it is usually appropriate to set it to 0.0005% by weight or more, preferably 0.001% by weight or more, for example, it can be 0.002% by weight or more, or it can be 0.0025% by weight or more. The upper limit of the content of the above-mentioned modified polyvinyl alcohol polymer (C1) is not particularly limited, for example, it can be set to 0.05% by weight or less. From the viewpoints of stability, polishing rate, cleaning properties, etc. in the concentrated liquid stage, in some embodiments, the content of the modified polyvinyl alcohol polymer (C1) is preferably 0.03% by weight or less, more preferably 0.015% by weight or less, and further preferably 0.01% by weight or less. The polishing liquid disclosed herein may be implemented, for example, in an embodiment in which the content of the modified polyvinyl alcohol polymer (C1) is 0.008 wt % or less, 0.006 wt % or less, 0.004 wt % or less, or 0.003 wt % or less.
[0154] Although not particularly limited, in some ways, from the viewpoint of improving surface quality, the content of the water-soluble polymer (C2) in the polishing liquid can be, for example, 0.0001% by weight or more, and it is usually appropriate to set it to 0.0005% by weight or more, preferably 0.001% by weight or more, 0.002% by weight or more, 0.003% by weight or more, or 0.004% by weight or more. The upper limit of the content of the above-mentioned water-soluble polymer (C2) is not particularly limited, for example, it can be set to less than 0.1% by weight. From the viewpoint of stability, polishing rate, cleaning properties, etc. in the concentrated liquid stage, in some ways, the content of the water-soluble polymer (C2) is preferably less than 0.05% by weight, more preferably less than 0.02% by weight, further preferably less than 0.01% by weight, and can be less than 0.005% by weight.
[0155] The total content of the water-soluble polymer in the polishing liquid (when comprising more than 2 kinds of water-soluble polymers, their total content) is not particularly limited, and in some ways, for example, can be set to more than 0.0001 weight %. From the viewpoints such as reducing haze, the above-mentioned total content is preferably more than 0.0005 weight %, more preferably more than 0.001 weight %, and further preferably more than 0.002 weight %, for example, can be more than 0.005 weight %. In addition, the upper limit of the above-mentioned total content is, for example, less than 0.5 weight %, and from the viewpoints such as polishing rate, it is preferably set to less than 0.2 weight %, more preferably set to less than 0.1 weight %, and further preferably set to less than 0.05 weight % (for example, less than 0.02 weight %, further less than 0.015 weight %).
[0156] Although not particularly limited, in some ways, from the viewpoints of improving surface quality, the content of the chelating agent in the polishing liquid can be, for example, more than 0.0001% by weight, and it is appropriate to usually set it to more than 0.0005% by weight, preferably more than 0.001% by weight, more than 0.0015% by weight, or more than 0.002% by weight. The upper limit of the content of the above-mentioned chelating agent is not particularly limited, for example, it can be set to less than 0.1% by weight. From the viewpoints of stability, polishing rate, cleaning properties, etc. in the concentrated solution stage, in some ways, the content of the chelating agent is preferably less than 0.05% by weight, more preferably less than 0.01% by weight, further preferably less than 0.008% by weight, or less than 0.006% by weight.
[0157] When a surfactant is included, the content of the surfactant in the polishing liquid (when two or more surfactants are included, the total content thereof) is not particularly limited as long as it does not significantly hinder the effect of the present invention. Usually, from the viewpoints of cleanability, the content of the above-mentioned surfactant can be, for example, set to more than 0.00001% by weight. From the viewpoints of reducing haze, the preferred content is more than 0.0002% by weight, more preferably more than 0.0003% by weight, and further preferably more than 0.0005% by weight. In addition, from the viewpoints of polishing rate, it is preferred that the above-mentioned content is set to less than 0.1% by weight, more preferably less than 0.01% by weight, and further preferably less than 0.005% by weight (for example, less than 0.002% by weight).
[0158] <Concentrate>
[0159] The grinding composition disclosed herein may be in a concentrated form (i.e., in the form of a concentrated solution of the grinding liquid) before being supplied to the substrate. This concentrated grinding composition is advantageous from the viewpoints of convenience, cost reduction, etc. during manufacture, circulation, and storage. The concentration ratio is not particularly limited, and for example, it may be set to be about 2 to 100 times in volume conversion, and generally about 5 to 50 times (e.g., about 10 to 40 times) is appropriate. Such a concentrated solution can be used in a manner of preparing a grinding liquid (working slurry) by diluting it at a desired time and supplying the grinding liquid to the substrate. The above-mentioned dilution can be performed, for example, by adding water to the above-mentioned concentrated solution and mixing it.
[0160] When the polishing composition (i.e., concentrated solution) is diluted and used for polishing, the content of the abrasive in the concentrated solution can be set to, for example, 25% by weight or less. From the viewpoints of dispersion stability and filterability of the polishing composition, the above content is usually preferably 20% by weight or less, more preferably 15% by weight or less. In some preferred embodiments, the content of the abrasive can be set to 10% by weight or less, or 5% by weight or less. In addition, from the viewpoints of convenience during manufacture, circulation, storage, etc., cost reduction, etc., the content of the abrasive in the concentrated solution can be set to, for example, 0.1% by weight or more, preferably 0.5% by weight or more, more preferably 0.7% by weight or more, and further preferably 1% by weight or more.
[0161] In some embodiments, the content of the alkaline compound in the above-mentioned concentrated solution can be set to, for example, less than 15% by weight. From the viewpoint of storage stability, the above-mentioned content is usually preferably 0.7% by weight or less, and more preferably 0.4% by weight or less. In addition, from the viewpoints of convenience during manufacture, circulation, storage, etc., cost reduction, etc., the content of the alkaline compound in the concentrated solution can be set to, for example, 0.005% by weight or more, preferably 0.01% by weight or more, more preferably 0.02% by weight or more, and further preferably 0.05% by weight or more.
[0162] In some embodiments, the total content of the water-soluble polymer in the above-mentioned concentrate can be set to, for example, 3% by weight or less. From the viewpoints of filterability and cleanability of the polishing composition, the above-mentioned content is usually preferably 1% by weight or less, and more preferably 0.5% by weight or less. In addition, from the viewpoints of convenience during manufacture, circulation, storage, etc., cost reduction, etc., it is appropriate that the above-mentioned content is usually 0.001% by weight or more, preferably 0.005% by weight or more, and more preferably 0.01% by weight or more.
[0163] In some embodiments, the content of the chelating agent in the above-mentioned concentrated solution can be set to, for example, 3% by weight or less. From the viewpoints of filterability and cleanability of the polishing composition, the above-mentioned content is usually preferably 1% by weight or less, and more preferably 0.5% by weight or less. In addition, from the viewpoints of convenience during manufacture, circulation, storage, etc., cost reduction, etc., the above-mentioned content is usually 0.01% by weight or more, preferably 0.05% by weight or more, and more preferably 0.1% by weight or more.
[0164] In the embodiment in which the polishing composition contains a surfactant, the content of the surfactant in the concentrated solution can be, for example, 0.25 wt% or less, preferably 0.15 wt% or less, more preferably 0.1 wt% or less, 0.05 wt% or less, or 0.025 wt% or less. In addition, the content of the surfactant in the concentrated solution can be, for example, 0.0001 wt% or more, preferably 0.001 wt% or more, more preferably 0.005 wt% or more, and even more preferably 0.01 wt% or more.
[0165] <Preparation of polishing composition>
[0166] The polishing composition used in the technology disclosed herein may be a single-component type or a multi-component type including a two-component type. For example, it may be composed in the following manner: a part A containing at least abrasive grains among the constituent components of the polishing composition is mixed with a part B containing at least a part of the remaining components, and these are mixed and diluted at an appropriate time as needed to prepare a polishing liquid.
[0167] The preparation method of the grinding composition is not particularly limited. For example, known mixing devices such as a blade stirrer, an ultrasonic disperser, and a homogenizer can be used to mix the components constituting the grinding composition. The embodiment of mixing these components is not particularly limited, for example, all the components can be mixed at once, or they can be mixed in a sequence appropriately set.
[0168] <Application>
[0169] The polishing composition disclosed herein can be applied to the polishing of substrates having various materials and shapes. The material of the substrate can be, for example, metals or semi-metals such as silicon materials, aluminum, nickel, tungsten, copper, tantalum, titanium, stainless steel, or their alloys; glassy substances such as quartz glass, aluminosilicate glass, and glassy carbon; ceramic materials such as aluminum oxide, silicon dioxide, sapphire, silicon nitride, tantalum nitride, and titanium carbide; compound semiconductor substrate materials such as silicon carbide, gallium nitride, and gallium arsenide; resin materials such as polyimide resins, etc. It can also be a substrate composed of multiple materials among them. The shape of the substrate is not particularly limited. The polishing composition disclosed herein can be applied to the polishing of substrates having a flat surface such as a plate or a polyhedron, or the polishing of the end of a substrate (such as the polishing of a wafer edge).
[0170] The polishing composition disclosed herein can be particularly preferably used for polishing a surface formed by a silicon material (typically polishing a silicon wafer). As specific examples of silicon materials, single crystal silicon, amorphous silicon and polycrystalline silicon etc. can be listed. The polishing composition disclosed herein can be particularly preferably used for polishing a surface formed by a single crystal silicon (e.g. polishing a silicon wafer).
[0171] The grinding composition disclosed herein can be preferably applied to the polishing process of a substrate (e.g., silicon wafer). For the substrate, before the polishing process performed using the grinding composition disclosed herein, general processing such as grinding and etching that can be applied to the substrate in a process further upstream of the polishing process can be implemented.
[0172] The grinding composition disclosed herein is effective for the finishing process of a substrate (e.g., a silicon wafer) or the polishing process immediately before it, and is particularly preferably used in the fine polishing process. Here, the fine polishing process refers to the last polishing process in the manufacturing process of the target object (i.e., a process in which no further polishing is performed after the process). In addition, the grinding composition disclosed herein can also be used for a polishing process upstream of the fine polishing (referring to a pre-polishing process between a rough grinding process and a final grinding process. Typically, it includes at least one polishing process, and further may include two, three, etc. polishing processes), for example, a polishing process performed immediately before the fine polishing.
[0173] The polishing composition disclosed herein is effective, for example, in the polishing (typically fine polishing or polishing immediately before) of a silicon wafer adjusted to a surface state of a surface roughness of 0.01 nm to 100 nm by an upstream process. It is particularly preferably applied to fine polishing. The surface roughness Ra of the substrate can be measured, for example, using a laser scanning surface roughness meter "TMS-3000WRC" manufactured by Schmitt MeasurementSystem Inc.
[0174] <Grinding>
[0175] The polishing composition disclosed herein can be used for polishing a substrate in a manner including the following operations, for example. A preferred embodiment of a method for polishing a silicon wafer as a substrate using the polishing composition disclosed herein will be described below.
[0176] That is, a polishing liquid comprising any of the polishing compositions disclosed herein is prepared. When preparing the above-mentioned polishing liquid, the step of preparing the polishing liquid by performing operations such as concentration adjustment (e.g., dilution) and pH adjustment on the polishing composition may be included. Alternatively, the polishing composition may be directly used as the polishing liquid.
[0177] Next, the polishing liquid is supplied to the substrate and polished by conventional methods. For example, in the case of fine polishing of a silicon wafer, typically, the silicon wafer that has undergone a grinding process is placed in a general polishing device, and the polishing liquid is supplied to the polishing target surface of the above-mentioned silicon wafer through the polishing pad of the polishing device. Typically, while the above-mentioned polishing liquid is continuously supplied, the polishing pad is pressed against the polishing target surface of the silicon wafer, and the two are moved relative to each other (for example, rotationally moved). After this polishing process, the polishing of the substrate is completed.
[0178] The grinding pad used in the above-mentioned grinding process is not particularly limited. For example, a foamed polyurethane type, a nonwoven type, a suede type or other grinding pads can be used. Each grinding pad can contain abrasive particles or can contain no abrasive particles. Usually, a grinding pad that does not contain abrasive particles is preferably used.
[0179] The substrate polished using the polishing composition disclosed herein is typically cleaned. Cleaning can be performed using an appropriate cleaning solution. The cleaning solution used is not particularly limited. For example, in the field of semiconductors, general SC-1 cleaning solution (a mixture of ammonium hydroxide (NH4OH), hydrogen peroxide (H2O2) and water (H2O)), SC-2 cleaning solution (a mixture of HCl, H2O2 and H2O), ozone water cleaning solution, hydrofluoric acid cleaning solution, etc. can be used. The temperature of the cleaning solution can be set, for example, to a range of above room temperature (typically about 15°C to 25°C) to about 90°C. From the viewpoint of improving the cleaning effect, a cleaning solution of about 50°C to 85°C can be preferably used.
[0180] As described above, the technology disclosed herein may include: providing a method for manufacturing a polished product (eg, a method for manufacturing a silicon wafer) including a polishing step (preferably fine polishing) using any of the above-mentioned polishing methods, and a polished product (eg, a silicon wafer) manufactured by the method.
[0181] Matters disclosed in this specification include the following.
[0182] [1] A polishing composition comprising: silica particles (A) as abrasive particles, a basic compound (B), a water-soluble polymer (C), and a chelating agent (D);
[0183] The water-soluble polymer (C) comprises a modified polyvinyl alcohol polymer (C1),
[0184] The etching rate of the modified polyvinyl alcohol polymer (C1) measured by the following etching rate is 20 nm / hour or less,
[0185] The etching rate is determined as:
[0186] (1) preparing a chemical solution LE for measuring an etching rate containing 0.175 wt % of a modified polyvinyl alcohol polymer and 0.205 wt % of ammonia, with the remainder being water;
[0187] (2) A silicon single crystal substrate (6 cm long, 3 cm wide, 775 μm thick rectangular shape) was prepared and its weight W0 was measured. The silicon single crystal substrate was immersed in a cleaning solution of NH4OH (29%):H2O2 (31%):deionized water (DIW) = 2:5.3:48 (volume ratio) at 25°C for 1 minute, and then immersed in a hydrogen fluoride (HF) aqueous solution (5%) at 25°C for 30 seconds;
[0188] (3) immersing the silicon single crystal substrate in the chemical solution LE at 25° C. for 40 hours;
[0189] (4) taking out the silicon single crystal substrate from the chemical solution LE and washing it with deionized water (DIW) at 25° C. for 10 seconds;
[0190] (5) measuring the weight W1 of the cleaned silicon single crystal substrate; and
[0191] (6) The etching rate [nm / hour] is calculated based on the difference between W0 and W1 and the specific gravity of the silicon single crystal substrate.
[0192] [2] The polishing composition according to [1] above, wherein the modified polyvinyl alcohol polymer (C1) is one or more selected from the group consisting of acetalized polyvinyl alcohol polymers and polyvinyl alcohol polymers containing repeating units derived from alkyl vinyl ethers.
[0193] [3] The polishing composition according to [1] or [2] above, wherein the content of the modified polyvinyl alcohol polymer (C1) is 0.5 parts by weight or more and 10 parts by weight or less per 100 parts by weight of the abrasive.
[0194] [4] The polishing composition according to any one of [1] to [3] above, further comprising a water-soluble polymer (C2) having a chemical structure different from that of the modified polyvinyl alcohol polymer (C1) as the water-soluble polymer (C),
[0195] The water-soluble polymer (C2) is a polymer containing nitrogen atoms.
[0196] [5] The polishing composition according to [4] above, wherein the nitrogen atom-containing polymer is a polymer containing a cyclic amide having an N-(meth)acryloyl group as a monomer unit.
[0197] [6] The polishing composition according to any one of [1] to [5] above, wherein the chelating agent (D) comprises one or more selected from the group consisting of aminocarboxylic acid chelating agents and organic phosphonic acid chelating agents.
[0198] [7] The polishing composition according to any one of [1] to [6] above, further comprising a surfactant (E).
[0199] [8] The polishing composition according to any one of [1] to [7] above, which is used for polishing a surface formed of a silicon material.
[0200] [9] A concentrated solution of the polishing composition according to any one of [1] to [8] above.
[0201]
[10] A polishing method comprising polishing a surface formed of a silicon material using the polishing composition according to any one of [1] to [9] above.
[0202] Example
[0203] Some embodiments related to the present invention are described below, but the present invention is not intended to be limited to the contents shown in these embodiments. It should be noted that in the following description, "parts" and "%" are based on weight unless otherwise specified.
[0204] <Preparation of polishing composition>
[0205] (Example 1)
[0206] Abrasive grains, alkaline compounds, water-soluble polymers, chelating agents, surfactants, and deionized water were mixed to prepare a concentrated solution of the polishing composition of each example. As the abrasive grains, colloidal silica with an average primary particle size of 25 nm was used. As the alkaline compound, ammonia was used. As the water-soluble polymer, acetalized polyvinyl alcohol (Ac-PVA; acetalization degree 24 mol%) with a Mw of about 9700 was used as the modified polyvinyl alcohol polymer (C1), and as the modified polyvinyl alcohol polymer (C2), with a Mw of about 35×10 4 Polyacryloylmorpholine (PACMO) was used as a water-soluble polymer (C2). Ethylenediaminetetra(methylenephosphonic acid) (EDTPO) was used as a chelating agent. Polyoxyethylene decyl ether (C10EO5) with an ethylene oxide addition mole number of 5 was used as a surfactant. The obtained concentrated solution of the polishing composition was diluted with deionized water to a volume ratio of 40 times, thereby obtaining polishing compositions of each example having an abrasive concentration of 0.15%, an alkaline compound concentration of 0.008%, an Ac-PVA concentration of 0.003%, a PACMO concentration of 0.005%, an EDTPO concentration of 0.003%, and a C10EO5 concentration of 0.0006%.
[0207] (Example 2)
[0208] Triethylenetetraaminehexaacetic acid (TTHA) was used as the chelating agent instead of EDTPO. The polishing composition of this example was prepared in the same manner as in Example 1 except that the concentration of TTHA was changed to 0.003%.
[0209] (Example 3)
[0210] As a chelating agent, trans-1,2-cyclohexanediaminetetraacetic acid (CyDTA) was used instead of EDTPO. In addition, the concentration of CyDTA was set to 0.003%. The polishing composition of this example was prepared in the same manner as in Example 1 except for this.
[0211] (Example 4)
[0212] A polishing composition of this example was prepared in the same manner as in Example 1 except that PACMO as the water-soluble polymer (C2) was not used.
[0213] (Example 5)
[0214] As a modified polyvinyl alcohol-based polymer (C1), an alkyl-modified PVA (hydrophobic-modified PVA) having a Mw of about 6100 was used instead of Ac-PVA. In addition, the concentration of the hydrophobic-modified PVA was set to 0.003%. The polishing composition of this example was prepared in the same manner as in Example 1. The alkyl-modified PVA used in this example is a random copolymer having vinyl alcohol units and n-propyl vinyl ether units in a molar ratio of 85:15.
[0215] (Comparative Example 1)
[0216] A polishing composition of this example was prepared in the same manner as in Example 1 except that no chelating agent was used.
[0217] (Comparative Example 2)
[0218] A polishing composition of this example was prepared in the same manner as in Example 1 except that PACMO as the water-soluble polymer (C2) and the chelating agent were not used.
[0219] (Comparative Example 3)
[0220] The Mw used is about 7.0×10 4 Completely saponified (saponification degree 98% or more) polyvinyl alcohol (PVA) was used instead of Ac-PVA. The concentration of PVA was set to 0.003%. The polishing composition of this example was prepared in the same manner as in Example 1 except for the above.
[0221] (Comparative Example 4)
[0222] A polishing composition of this example was prepared in the same manner as in Example 1 except that a butene glycol-vinyl alcohol copolymer (BVOH) was used instead of Ac-PVA and the concentration of BVOH was changed to 0.003%.
[0223] The outline of the structure of each example is shown in Table 1. In addition, the etching rate of the water-soluble polymer used in each example was determined based on the etching rate measurement. The obtained results are shown in the "etching rate" column of Table 1.
[0224] <LPD-N evaluation>
[0225] [Polishing of silicon wafers]
[0226] As a substrate, a commercially available single crystal silicon wafer (conductive type: P type, crystal orientation: <100>, no COP (Crystal Originated Particle: crystal defect)) with a diameter of 300 mm that had been ground and etched was prepared and pre-polished according to the following polishing condition 1. The pre-polishing was performed using a polishing liquid containing 0.6% abrasive (colloidal silica with an average primary particle size of 35 nm) and 0.08% tetramethylammonium hydroxide (TMAH) in deionized water.
[0227] [Grinding Condition 1]
[0228] Grinding device: Okamoto Machine Tool Co., Ltd. single-wafer grinding device model "PNX-332B"
[0229] Grinding load: 20kPa
[0230] Plate speed: 20rpm
[0231] Grinding head (carrier) speed: 20rpm
[0232] Polishing pad: Made by NITTA DuPont Incorporated. Product name: "SUBA400"
[0233] Polishing fluid supply speed: 1.0L / min
[0234] Grinding fluid temperature: 20°C
[0235] Plate cooling water temperature: 20℃
[0236] Grinding time: 2 minutes
[0237] The silicon wafer after the preliminary polishing was polished according to the following polishing condition 2 using the polishing composition of each example prepared above as a polishing liquid, and then polished according to the following polishing condition 3.
[0238] [Grinding Condition 2]
[0239] Grinding device: Okamoto Machine Tool Co., Ltd. single-wafer grinding device model "PNX-332B"
[0240] Grinding load: 16kPa
[0241] Plate speed: 52rpm
[0242] Grinding head (carrier) speed: 50rpm
[0243] Polishing pad: FUJIBO Ehime Co., Ltd., product name "POLYPAS275NX"
[0244] Grinding liquid supply rate: 1.5L / min
[0245] Grinding fluid temperature: 20°C
[0246] Plate cooling water temperature: 20℃
[0247] Grinding time: 2 minutes
[0248] [Grinding Condition 3]
[0249] Grinding device: Okamoto Machine Tool Co., Ltd. single-wafer grinding device model "PNX-332B"
[0250] Grinding load: 20kPa
[0251] Plate speed: 52rpm
[0252] Grinding head (carrier) speed: 50rpm
[0253] Polishing pad: FUJIBO Ehime Co., Ltd., product name "POLYPAS27NX"
[0254] Grinding liquid supply rate: 1.5L / min
[0255] Grinding fluid temperature: 20°C
[0256] Plate cooling water temperature: 20℃
[0257] Grinding time: 2 minutes
[0258] The ground silicon wafer was removed from the grinding device and cleaned with ozone water cleaning liquid (60 seconds) using a single-wafer cleaning device, followed by cleaning with SC-1 cleaning liquid and a brush (110 seconds), followed by cleaning with ozone water cleaning liquid (20 seconds) and cleaning with hydrofluoric acid cleaning liquid (15 seconds) as one set, for a total of 3 sets, and then cleaning with ozone water cleaning liquid (20 seconds). The silicon wafer was then dried.
[0259] The number of LPD-N on the surface of the cleaned silicon wafer was measured using a wafer inspection device, trade name "Surfscan SP5" manufactured by KLA Corporation, in the DC mode of the device. The number of LPD-N measured was converted into a relative value with the number of LPD-N in Comparative Example 1 being 100%. The obtained results are shown in the "LPD-N" column of Table 1.
[0260] <Evaluation of polishing rate>
[0261] [Polishing of silicon wafers]
[0262] A commercially available single crystal silicon wafer with a diameter of 300 mm (conductivity type: P type, crystal orientation: <100>, no COP (Crystal Originated Particle)) that had been ground and etched was polished under the following polishing condition 4 using the polishing composition of each example prepared above as a polishing liquid.
[0263] [Grinding Condition 4]
[0264] Grinding device: Okamoto Machine Tool Co., Ltd. single-wafer grinding device model "PNX-322"
[0265] Grinding load: 10kPa
[0266] Plate speed: 52rpm
[0267] Grinding head (carrier) speed: 50rpm
[0268] Polishing pad: FUJIBO Ehime product name "POLYPAS275NX"
[0269] Grinding liquid supply rate: 0.75L / min
[0270] Grinding fluid temperature: 20°C
[0271] Plate cooling water temperature: 20℃
[0272] Grinding time: 10 minutes
[0273] The ground silicon wafer was removed from the grinding device and cleaned by immersing it in ozone water cleaning liquid at room temperature for 15 minutes. Then, the silicon wafer was dried using a spin dryer.
[0274] (Evaluation of polishing rate)
[0275] Based on the weight difference of the wafer before and after the 10-minute polishing, the polishing rate R [cm / min] in each embodiment and comparative example was calculated according to the following formulas (a1) to (a3). The obtained polishing rate R was converted into a relative value with the polishing rate of Comparative Example 1 as 100%. The obtained results are shown in the "Polishing Rate" column of Table 1. If the polishing rate (relative value) is 70% or more, it is evaluated as maintaining the polishing rate.
[0276] Mode:
[0277] ΔV=(W0-W1) / d (a1)
[0278] Δx=ΔV / S (a2)
[0279] R=Δx / t (a3)
[0280] ΔV: Change in wafer volume before and after grinding
[0281] W0: Wafer weight before grinding [g]
[0282] W1: Wafer weight after grinding [g]
[0283] d: specific gravity of silicon (2.33) [g / cm 3 ]
[0284] S: Wafer surface area [cm 2 ]
[0285] Δx: Change in wafer thickness before and after grinding [cm]
[0286] t: grinding time [min]
[0287] The column "LPD-N / polishing rate" in Table 1 shows the ratio of LPD-N (relative value) to the polishing rate (relative value) calculated from the polishing rate (relative value) and LPD-N (relative value) of each example obtained based on the above method. The smaller the above ratio is, the more LPD-N tends to be reduced while maintaining the polishing rate.
[0288] [Table 1]
[0289]
[0290] As shown in Table 1, in Examples 1 to 5 using polishing compositions containing silica particles, an alkaline compound, a modified polyvinyl alcohol polymer having an etching rate of 20 nm / hour or less (modified polyvinyl alcohol polymer (C1)), and a chelating agent, compared to Comparative Examples 1 to 4 using polishing compositions not using a chelating agent and / or a modified polyvinyl alcohol polymer having an etching rate of 20 nm / hour or less, it was confirmed that the amount of LPD-N was significantly reduced while the polishing rate was basically maintained, thereby achieving high surface quality. In particular, from the comparison between Example 1 and Comparative Example 1 and the comparison between Example 4 and Comparative Example 2, it was confirmed that in a system containing a modified polyvinyl alcohol polymer having an etching rate of 20 nm / hour or less (modified polyvinyl alcohol polymer (C1)), the addition of a chelating agent reduced LPD-N and improved the polishing rate. Furthermore, from the comparison between Examples 1 to 5 and Comparative Examples 3 and 4, it was confirmed that when a modified polyvinyl alcohol polymer having an etching rate of 20 nm / hour or less was used, the number of LPD-N tended to be significantly reduced while maintaining the polishing rate.
[0291] Although specific examples of the present invention have been described in detail above, these are merely examples and do not limit the claims. The technology described in the claims includes various modifications and changes to the specific examples described above.
Claims
1. A polishing composition comprising: silica particles (A) as abrasive particles, a basic compound (B), a water-soluble polymer (C) and a chelating agent (D), The water-soluble polymer (C) comprises a modified polyvinyl alcohol polymer (C1), The etching rate of the modified polyvinyl alcohol polymer (C1) measured by the following etching rate is 20 nm / hour or less, The etching rate is determined as: (1) preparing a chemical solution LE for measuring an etching rate containing 0.175 wt % of a modified polyvinyl alcohol polymer and 0.205 wt % of ammonia, with the remainder being water; (2) A rectangular silicon single crystal substrate with a length of 6 cm, a width of 3 cm, and a thickness of 775 μm was prepared and its weight W0 was measured. The silicon single crystal substrate was immersed in a cleaning solution of NH4OH (29%):H2O2 (31%):deionized water (DIW) = 2:5.3:48 (volume ratio) at 25°C for 1 minute, and then immersed in a hydrogen fluoride (HF) aqueous solution (5%) at 25°C for 30 seconds; (3) immersing the silicon single crystal substrate in the chemical solution LE at 25° C. for 40 hours; (4) taking out the silicon single crystal substrate from the chemical solution LE and washing it with deionized water (DIW) at 25° C. for 10 seconds; (5) measuring the weight W1 of the cleaned silicon single crystal substrate; and (6) The etching rate [nm / hour] is calculated based on the difference between W0 and W1 and the specific gravity of the silicon single crystal substrate.
2. The polishing composition according to claim 1, wherein The modified polyvinyl alcohol-based polymer (C1) is one or more selected from the group consisting of acetalized polyvinyl alcohol-based polymers and polyvinyl alcohol-based polymers containing repeating units derived from alkyl vinyl ethers.
3. The polishing composition according to claim 1 or 2, wherein The content of the modified polyvinyl alcohol-based polymer (C1) is 0.5 parts by weight or more and 10 parts by weight or less based on 100 parts by weight of the abrasive.
4. The polishing composition according to claim 1 or 2, further comprising a water-soluble polymer (C2) having a chemical structure different from that of the modified polyvinyl alcohol polymer (C1) as the water-soluble polymer (C), The water-soluble polymer (C2) is a polymer containing nitrogen atoms.
5. The polishing composition according to claim 4, wherein The nitrogen atom-containing polymer is a polymer containing a cyclic amide having an N-(meth)acryloyl group as a monomer unit.
6. The polishing composition according to claim 1 or 2, wherein The chelating agent (D) includes one or more selected from the group consisting of aminocarboxylic acid chelating agents and organic phosphonic acid chelating agents. 7 . The polishing composition according to claim 1 , further comprising a surfactant (E).
8. The polishing composition according to claim 1 or 2, which is used for polishing a surface formed of a silicon material.
9. The concentrated polishing composition according to claim 1 or 2. 10 . A polishing method comprising polishing a surface formed of a silicon material using the polishing composition according to claim 1 or 2.
Citation Information
Patent Citations
Reducing of metal oxide containing material
JP1987032243B2
Continuous annealing furnace of meal strip
JP1988048927B2
Optical sensor device
JP2022125594A